Coherent libration to coherent rotational dynamics via chimeralike states and clustering in a Josephson junction array - Mishra, Arindam; Saha, Suman; Hens, Chittaranjan; Roy, Prodyot K.; Bose, Mridul; Louodop, Patrick [UNESP]; Cerdeira, Hilda A. [UNESP]; Dana, Syamal K. (Amer Physical Soc, 2017)
An array of excitable Josephson junctions under a globalmean-field interaction and a common periodic forcing shows the emergence of two important classes of coherent dynamics, librational and rotational motion, in the weaker and stronger coupling limits, respectively, with transitions to chimeralike states and clustered states in the intermediate coupling range. In this numerical study, we use the Kuramoto complex order parameter and introduce two measures, a libration index and a clustering index, to characterize the dynamical regimes and their transitions and locate them in a parameter plane.